Effects of Aerobic and Resistance Exercises on Physical Symptoms in Cancer Patients: A Meta-analysis. (December 2018) - Nakano, Jiro; Hashizume, Kaori; Fukushima, Takuya; Ueno, Kazumi; Matsuura, Emi; Ikio, Yuta; Ishii, Shun; Morishita, Satoru; Tanaka, Koji; Kusuba, Yoko
Objective . This study aimed to conduct a meta-analysis to establish the effect of exercise interventions on physical symptoms, including fatigue, nausea/vomiting, pain, dyspnea, insomnia, loss of appetite, constipation, and diarrhea in cancer patients and survivors. Methods . We searched articles published before April 2017 using the following databases: Cochrane Library, PubMed/MEDLINE, CINAHL, Scopus, PEDro, Health & Medical Collection, and Psychology Database. Randomized controlled trials (RCTs) of exercise intervention in cancer patients, which evaluated cancer-related physical symptoms using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30, were included. Symptom scale data were extracted for meta-analysis. Subgroup analyses were performed for exercise types (aerobic, resistance, and mixed exercise programs). Results . Of the 659 articles, 10 RCTs were included in the meta-analysis, of which the mean PEDro score was 5.43 (SD = 1.28). Fatigue, pain, dyspnea, and insomnia were significantly lower in the intervention group than in the control group at postintervention in cancer patients. However, exercise intervention did not promote or suppress nausea/vomiting, loss of appetite, constipation, and diarrhea in cancer patients. The effect of exercise type on each symptom was not different. Conclusion. Exercise intervention was confirmed to improve fatigue, pain, and insomnia and might have reduced dyspnea in cancer patients. However, the benefits of exercise on nausea/vomiting, loss of appetite, constipation, and diarrhea were not shown in any exercise type. Further research is warranted to examine the effects of exercise interventions on physical symptoms in cancer patients.